Optimizing Thermal Comfort with Adaptive Behaviours in South Australian Residential Buildings - Szymon Firląg; Artur Miszczuk (Energies)
This study focuses on thermal comfort in residential buildings within the Iron Triangle area of South Australia, examining how indoor conditions influence residents’ comfort and adaptive behaviours. Conducted from June 2023 to February 2024 across 30 homes in Port Pirie, Port Augusta, and Whyalla, the research gathered data from 38 residents, who reported indoor comfort levels in living rooms and bedrooms. A total of 3540 responses were obtained. At the same time, the measurement of indoor conditions in the buildings was performed using a small HOBO MX1104 device. Using the Mean Thermal Sensation Vote (MTSV) concept, it was possible to determine the neutral operative temperature and temperature ranges for thermal comfort categories. According to the defined linear regression formula, the neutral temperature was 23.9 °C. In living rooms, it was slightly lower, at 23.7 °C, and in bedrooms, slightly higher, at 24.4 °C. For comparison, the neutral temperature was calculated based on the average Predicted Mean Vote (MPMV) and equal to 24.3 °C. Comparison of the regression curves showed that in terms of slope, the MPMV curve is steeper (slope 0.282) than the MTSV curve (slope 0.1726), and lies above it. Regarding the residents’ behaviour, a strong correlation was found between the operative temperature To and the degree of clothing Icl in living rooms. Use of ceiling fans was also studied. A clear trend was also observed regarding window and door opening. The findings of the research can be used to inform the design and operation of residential buildings with a view to enhancing thermal comfort and energy efficiency.